The implications of the Pineo Ridge readvance in Maine - Borns, Harold; Hughes, Terence (Géographie physique et Quaternaire)

(untitled) (Les Presses de l’Université de Montréal, 1977)
Much of the Laurentide ice sheet in Maine, Atlantic Provinces, and southern Quebec was a "marine ice sheet," that is it was grounded below the prevailing sea level. When proper conditions prevailed, calving bays progressed into the ice sheet along ice streams partitioning it, leaving those portions grounded above sea level as residual ice caps. At least by 12,800 yrs. BP a calving bay had progressed up the St. Lawrence Lowland at least to Ottawa while a similar, but less extensive calving bay developed in Central Maine at approximately the same time. Concurrently, ice draining north into the St. Lawrence and south into the Central Maine calving bays rapidly lowered the surface of the intervening ice sheet until it eventually divided over the NE-SW trending Boundary and Longfellow Mountains and probably over other highland areas as well. A major consequence of these nearly simultaneous processes was the separation of an initial large ice cap over part of Maine, New Brunswick, and Québec which was bounded on the west by the calving bay in Central Maine, to the north by the calving bay in the St. Lawrence Lowland, to the south by the Bay of Fundy, and to the east by the Gulf of St. Lawrence. In coastal Maine, east of the calving bay, the margin of the ice cap receded above the marine limit at least 40 km and subsequently read-vanced terminating at Pineo Ridge moraine approximately 12,700 yrs. BP. These events are the stratigraphie and chronologic equivalent of the Cary-Pt. Huron recession/Pt. Huron readvance of the Great Lakes region.